Presence of Two Distal and One Mesial Root Canals in Mandibular Second Molars: Report of Four Cases - Parirokh, Masoud; Abbott, Paul V; Yosefi, Mohammad Hosein; Hosseini, Hamid Reza (Iranian Endodontic Journal, 2014)
Most mandibular second molars have one and two canals in distal and mesial roots, respectively. This report represents four cases of mandibular second molars with a single mesial and two distal root canals with two different canal configurations. After access cavity preparation, two teeth had one distal and two mesial orifices, whereas in the two other teeth one mesial and two distal orifices were found. In the teeth with two mesial canal orifices, the distal root canal and one of root canals with a mesial orifice joined together in the apical part of the root, whereas in the two other teeth with one mesial and two distal canal orifices, three separate canals each with a different apical foramen were detected. Dental practitioners should be aware that despite higher prevalence of one distal and two mesial root canals, the mandibular second molar teeth may also have one mesial and two distal root canals.